Physical activity changes in the winter in older persons living in northern Japan: a prospective study - Mizumoto, Atsushi (BMC Geriatr, 2015)
BACKGROUND: Physical activity affects physical and mental health, prevents disease, and improves quality of life. However, physical activity also decreases with age in older persons, and is affected by adverse climatic periods. This study examined changes in physical activity during the winter season in older persons (≥75 years of age) who were living in northern Japan, and evaluated the factors that were associated with this decline. METHODS: A total of 201 older persons (83 men and 118 women; mean age, 79.7 ± 3.8 years) participated in two separate tests that were conducted in November 2012 and February 2013. Physical activity was monitored using the Kenz Lifecorder, and mean step counts and moderate-vigorous physical activity (MVPA) times were calculated over a 1-week period. We also measured body mass index, handgrip strength, normal walking speed, functional capacity, exercise habits, snow-shovelling habits, a change in frequency (between early winter and midwinter) of outdoor excursions, the length of outdoor excursions, social support, and morbidity. RESULTS: In the group that maintained their frequency of outdoor excursions, step counts significantly increased during midwinter compared with early winter (p < 0.01). In the group with a lower frequency of outdoor excursions, MVPA was significantly decreased during midwinter compared with early winter (p < 0.05). After adjusting for other variables, logistic regression analysis showed that weakness (odds ratio [OR]: 2.89, p < 0.05) was independently associated with a decline in step counts. Age (OR: 1.12, p < 0.05) and a change in frequency of outdoor excursions (OR: 0.75, p < 0.01) were independently associated with a decline in MVPA. CONCLUSIONS: Older persons should be supported in their attempts to go outdoors during midwinter. They should be provided with intervention programs to increase their physical activity at home.